A Comparative Analysis of Manual and Computer Constant Comparison Methods: Using Data from a Constructivist Inquiry of Experiences Working with Ethnic Agencies - Suzie Weng (Social Work and Society)
A dilemma one may face in analyzing qualitative data is whether to use a manual approach with index cards or a computer data management tool like ATLAS.ti.  This paper compares the two approaches in organizing and analyzing data using the same data set.  The data were collected and first analyzed in a constructivist inquiry course according to the methods laid out by Rodwell (1998).  This process involved unitizing data onto index cards and these cards were then sorted into categories during the constant comparison process.  Later, the same data were linked to ATLAS.ti where they were unitized and categorized simultaneously.  Constant comparison took place when all the data were coded.  A comparison of the two methods allowed the author to determine the strengths and limitations for the various stages of constant comparison.